2016
DOI: 10.5664/jcsm.6358
|View full text |Cite
|
Sign up to set email alerts
|

High School Start Times and the Impact on High School Students: What We Know, and What We Hope to Learn

Abstract: Study Objectives: Several organizations have provided recommendations to ensure high school starts no sooner than 08:30. However, although there are plausible biological reasons to support such recommendations, published recommendations have been based largely on expert opinion and a few observational studies. We sought to perform a critical review of published evidence regarding the effect of high school start times on sleep and other relevant outcomes. Methods: We performed a broad literature search to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
3
33
0
2
Order By: Relevance
“…Our findings suggest that adolescents' chronotypes are on average too late for school start times before 8:30 a.m., i.e., many may not be able to advance their sleep enough to get sufficient sleep, which is in line with another CDC report showing that 68.8% of US high school students sleep less than 8h during an average school night [32]. Evidence is mounting that one simple and effective (yet not the only) way to benefit adolescent sleep is to delay school start times [33].…”
Section: Adolescents Are On Average the Latest Chronotypessupporting
confidence: 67%
“…Our findings suggest that adolescents' chronotypes are on average too late for school start times before 8:30 a.m., i.e., many may not be able to advance their sleep enough to get sufficient sleep, which is in line with another CDC report showing that 68.8% of US high school students sleep less than 8h during an average school night [32]. Evidence is mounting that one simple and effective (yet not the only) way to benefit adolescent sleep is to delay school start times [33].…”
Section: Adolescents Are On Average the Latest Chronotypessupporting
confidence: 67%
“…Unlike previous works [103][104][105][106], systematic and meta-analytic analysis is beyond the scope of this review, and this entailed some basic limitations. Indeed, a rigorous methodological quality review of the included literature was not undertaken, and, consequently, some of the cited studies are less rigorous and have more potential bias than others.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic [103][104][105] and meta-analytic [106] reviews provided a qualitative and quantitative synthesis of the strength of delayed school programs in improving several sleep-related outcome variables. The outcomes, mostly estimated by sleep habits survey, illustrated the effectiveness of these programs on rising time, bedtime, or time spent in sleeping.…”
Section: Benefits and Challenges Of Delayed School Start Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Further support for a positive effect of later SSTs on sleep duration, as well as reduced car accidents and daytime sleepiness, was provided in a recent evidence-based review. 37 However, this study found only weak evidence overall for the association of later SSTs and improved academic performance and behavioral health.…”
Section: Increased Support For Later School Start Times May Require Ementioning
confidence: 69%